Water Uptake in PHBV/Wollastonite Scaffolds: A Kinetics Study - Ribas, Renata G.; Montanheiro, Thais L. A.; Montagna, Larissa S.; Prado, Renata Falchete do [UNESP]; Lemes, Ana Paula; Bastos Campos, Tiago M.; Thim, Gilmar P. (Mdpi, 2019)
Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) is a widely studied polymer and it has been found that porous PHBV materials are suitable for substrates for cell cultures. A crucial factor for scaffolds designed for tissue engineering is the water uptake. This property influences the transport of water and nutrients into the scaffold, which promotes cell growth. PHBV has significant hydrophobicity, which can harm the production of cells. Thus, the addition of alpha-wollastonite (WOL) can modify the PHBV scaffold's water uptake. To our knowledge, a kinetics study of water uptake of alpha-wollastonite phase powder and the PHBV matrix has not been reported. In this work, PHBV and WOL, (PHBV/WOL) films were produced with 0, 5, 10, and 20 wt % of WOL. Films were characterized, and the best concentrations were chosen to produce PHBV/WOL scaffolds. The addition of WOL in concentrations up to 10 wt % increased the cell viability of the films. MTT analysis showed that PHBV/5%WOL and PHBV/10%WOL obtained cell viability of 80% and 98%, respectively. Therefore, scaffolds with 0, 5 and 10 wt % of WOL were fabricated by thermally induced phase separation (TIPS). Scaffolds were characterized with respect to morphology and water uptake in assay for 65 days. The scaffold with 10 wt % of WOL absorbed 44.1% more water than neat PHBV scaffold, and also presented a different kinetic mechanism when compared to other samples. Accordingly, PHBV/WOL scaffolds were shown to be potential candidates for biological applications.
Keywords: poly(3-hydroxybutyrate-co-3-hydroxyvalerate); wollastonite; composites; scaffolds; kinetics; water absorption